Effect of serum uric acid level on reproductive outcome in women without polycystic ovary syndrome undergoing in vitro fertilization - Leizhen Xia; Lu Fan; Jialyu Huang; Yan Zhao; Lifeng Tian; Houyang Chen; Li Cai; Qiongfang Wu; Leixiang Xia (BMC, 2024)
Abstract Background Prior research showed that elevated serum uric acid (SUA) levels in women with polycystic ovary syndrome (PCOS) before in vitro fertilization or intracytoplasmic sperm injection (IVF/ICSI) treatment can lead to a lower rate of live birth and an increased risk for low birthweight. Nonetheless, it is not known whether elevated SUA results in similar reproductive outcome in women without PCOS. This study aimed to exploring the relationship between pre-pregnancy SUA levels and reproductive outcomes in non-PCOS women undergoing IVF/ICSI treatment. Methods This single-center, retrospective study included 13,325 women without PCOS undergoing their first IVF/ICSI fresh embryo transfer cycles from January 2014 to December 2022 at a university-affiliated reproductive medicine center in China. The trends for pregnancy, obstetric and perinatal outcomes across quartiles of SUA levels were assessed. A logistic regression analysis was applied to control for baseline and cycle characteristics. Generalized addition model was used to draw spline smoothing plot. Results There was no significant decreasing or increasing trend in the clinical pregnancy rate and live birth rate with the increase in quartiles of SUA levels. For Obstetric and perinatal outcomes following a single live birth, the percentage of hypertensive disorders in pregnancy (1.6-4.1%, P trend<0.001), gestational diabetes mellitus (5.9-13.9%, P trend<0.001), premature rupture of membranes (0.6-1.5%, P trend=0.016), preterm birth (6.3-9.2%, P trend=0.009), macrosomia (2.3-5.5%, P trend<0.001), large for gestational age (10.8-14.9%, P trend=0.002) all increased significantly from the lowest quartile to the highest. Logistic regression results showed that compared with those in quartile 1, the risk of maternal and infant complications mentioned above was still significantly higher in quartile 4 after adjusting for reproductive related factors. When further confounding factors were added, including body mass index (BMI), blood pressure, fasting blood glucose, and blood lipids related indicators, only gestational diabetes mellitus and macrosomia showed a significant increase. Conclusion In women without PCOS, SUA levels before IVF/ICSI treatment do not affect the probabilities of clinical pregnancy and live birth. An elevated SUA level is associated with an increased risk for hypertensive disorders in pregnancy, gestational diabetes mellitus, premature rupture of membranes, preterm birth, macrosomia, and large for gestational age. For gestational diabetes mellitus and macrosomia, the association is independent of BMI, blood pressure, blood glucose, and blood lipid.